KEWENANGAN KANTOR OTORITAS BANDARA WILAYAH IV DALAM PENEGAKAN HUKUM TERHADAP PEMALSUAN PAS BANDARA - Susanto, Joko; Sukardi, Ni Made Rai (Jurnal Ilmiah Raad Kertha, 2024)
The number of incidents of counterfeiting airport pas poses a risk of threats to aviation security that can result in aviation law violations, for that law enforcement is needed in order to provide a deterrent effect while realizing legal certainty against perpetrators of airport passport forgery. The formulation of the problem in this study is how the authority of the Region IV Airport Authority Office in law enforcement against counterfeiting airport pas, as well as what factors hinder law enforcement against counterfeiting airport pas, the objectives of this study are, first, to determine the authority of the Region IV Airport Authority Office in law enforcement against counterfeiting airport pas, second, to determine the factors that hinder law enforcement against counterfeiting airport pas. The research approach used is normative juridical, the normative juridical approach seeks to understand the law from a theoretical and philosophical perspective. This research uses normative legal research methods by analyzing various legal sources such as constitutions, laws, court decisions, legal doctrines, and opinions of legal experts. The results of this study are first, the authority of the Region IV Airport Authority Office in law enforcement against counterfeiting airport pas has not been maximized, as evidenced by the Region IV Airport Authority Office has never taken action in court against counterfeiting airport pas. Second, the factor that hinders the law enforcement of airport pass forgery is that the Region IV Airport Authority Office does not yet have the authority to investigate the criminal offense of airport pas forgery.